2016
DOI: 10.1111/den.12639
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for endoscopic management of non‐variceal upper gastrointestinal bleeding

Abstract: Japan Gastroenterological Endoscopy Society (JGES) has compiled a set of guidelines for endoscopic management of non‐variceal upper gastrointestinal bleeding using evidence‐based methods. The major cause of non‐variceal upper gastrointestinal bleeding is peptic gastroduodenal ulcer bleeding. As a result, these guidelines mainly focus on peptic gastroduodenal ulcer bleeding, although bleeding from other causes is also overviewed. From the epidemiological aspect, in recent years in Japan, bleeding from drug‐rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 205 publications
(434 reference statements)
1
91
2
2
Order By: Relevance
“…In this study, the percentage of UGIB caused by H. pylori -related peptic ulcer was decreased markedly between the 2 time periods of the study, which is compatible with the findings of previous studies [1,2,7,9,11]. Concomitant with the decrease in proportion of H. pylori -related peptic ulcer, the ratio of study patients with a previous history of peptic ulcer was lower in the second period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the percentage of UGIB caused by H. pylori -related peptic ulcer was decreased markedly between the 2 time periods of the study, which is compatible with the findings of previous studies [1,2,7,9,11]. Concomitant with the decrease in proportion of H. pylori -related peptic ulcer, the ratio of study patients with a previous history of peptic ulcer was lower in the second period.…”
Section: Discussionsupporting
confidence: 91%
“…Helicobacter pylori infection and the use of nonsteroidal, antiinflammatory drugs (NSAIDs), including aspirin, are the main causes of bleeding peptic ulcer diseases [1,2]. H. pylori infection was previously widespread in Japan, which resulted in a relatively low incidence of H. pylori -negative ulcers [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of PPIs is reportedly useful for preventing low-dose aspirin prevent ulcer bleeding and death [10]. Moreover, PPI administration is recommended in the Japanese guidelines [11], and national health insurance treatment is considered to boost the high rate of prophylaxis administration in ­Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The outpatients were further classified into 2 subgroups: those who visited the hospital emergency unit during regular hours (08: 30 to 17: 00 on weekdays; n  = 120) and those who visited the hospital emergency unit during off hours (17: 00 to 8: 30 on weekdays or on weekends/holidays; n  = 187). Hemostasis was achieved in all patients in the present study with endoscopic maneuvers including hemoclip application, pure ethanol injection and/or electrocoagulation, as previously described [1, 2, 11-13]. After endoscopic hemostasis, all patients were hospitalized and managed with conventional therapies, including nil oral intake, intravenous fluids and acid secretion inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Emergency endoscopic hemostasis is the primary therapeutic approach to upper gastrointestinal bleeding, which is a serious life-threatening condition [1, 2]. Several studies in Western countries have indicated a “weekend effect” in therapeutic outcomes of endoscopic hemostasis in patients with upper gastrointestinal bleeding: those treated during off hours had a worse prognosis than those treated during regular hours [3-6].…”
Section: Introductionmentioning
confidence: 99%